The Pathogenesis of Fungal Coinfections in COVID-19 Cases: A Literature Review - Hanifah, Rifdah; Yasmon, Andi (Poltekkes Kemenkes Kendari, 2023)
Coronavirus disease 2019 (COVID-19) is a disease that attacks the human respiratory tract caused by the SARS-CoV2 virus. Critically ill patients admitted to the ICU, require a ventilator or are hospitalized for a long time are susceptible to fungal coinfection. Several fungi were detected to cause coinfection with COVID-19, such as Candida spp, Aspergillus spp, Mucor spp, and Cryptococcus spp. Research on the mechanism of fungal infection in COVID-19 patients still requires further research, but several possibilities can be associated with both. Several factors that can cause fungal coinfection, including the use of corticosteroids, ventilators, and oxygen masks in COVID-19 patients. The condition of immune dysregulation in COVID-19 patients causes the patient’s body to be unable to fight fungal infections. Some prevention can be done by regularly coordinating the early detection of fungal infections in COVID-19 patients to reduce risk factors and improve routine treatment protocols. If the patient has a fungal infection, treatment can be done using some of the recommended drug combinations. In addition, to maintain the cleanliness of medical devices, especially ventilators, the cleanliness of hospital wards, and the process of handling COVID-19 patients, it is also necessary to pay attention to preventing the transmission of COVID-19 hospitalized patients.